DAMPAK EKONOMI KREATIF TERHADAP PEMBERDAYAAN MASYARAKAT - Nur Dika Dewi (CURVE: Journal of Economic, Business and Accounting, 2025)
The creative economy has become a dynamic and rapidly growing economic sector in the past two decades, driven by advances in digital technology, cultural globalization, and increasing awareness of the value of creativity and innovation. This study aims to understand the influence of the creative economy on community empowerment in specific sectors, to measure its contribution to increasing income, skills, or community independence. Furthermore, it provides theoretical and practical benefits for policymakers, business actors, and local communities. This study uses a quantitative approach with a survey method to investigate the relationship between creative economy variables and community empowerment. The study population included creative economy entrepreneurs and empowered communities in specific regions, using purposive sampling or stratified random sampling. The results of this study indicate that digital literacy has the most significant influence on community empowerment through the creative economy because digital literacy connects creative actors with global markets and marketing technology. Furthermore, entrepreneurial orientation and socio-cultural engagement are also key factors supporting the success of empowerment.